Golden Obstacle - Priemus, Jessica (2019)
This work examines how the unravelled thread can affect the spatial and temporal understanding of a greater woven textile. Methods centred on processes of undoing, disentangling, deconstruction and reconstruction of isolated elements/threads. The textile-like fibrous sheath from a palm tree frond was deconstructed and separate threads reconstructed into one large thread, bound with golden yarn. Despite trying to create something linear, the reconstructed piece took on its own snaking and chaotic form. This challenged the notion of the thread as flat and linear, and a textile’s intrinsic adherence to ‘the grid’.